Peran Kepuasan dalam Memediasi Hubungan Kualitas Pelayanan dan Harga pada Loyalitas Pelanggan di E-Commerce Shopee - Tsamara Aulia Yumna; Siti Almaidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of marketing today is no longer limited to time and space. This condition is caused by technological advances that are very supportive of conducting marketing activities in a wider scope. Both for service and non-service offerings. Along with the growth of demand by consumers through online, market place platforms have emerged that offer various consumer needs. So there is sharp competition among sellers. These conditions require companies to pay attention to the satisfaction felt by consumers which will ultimately create loyal consumers. The company should also consider the different elements that influence it. The focus of this research is to analyze how customer satisfaction mediates the relationship between service quality and price on loyalty. The sample involved was 80 Shopee e-commerce customers. Data testing includes, data quality test, classic assumption test, outlier test, and path analysis. A significant discovery is that satisfaction does not serve as a mediator in the relationship between service quality, price, and customer loyalty.